Sequence of 863 nucleotides encompassing the PstI site of the yeast 2 micron plasmid. - Elleman, T C (1980)
The sequence of part of the larger unique region of the yeast 2 micron plasmid cloned in pMB9 has been determined. The sequence extends from the single EcoRI site in this region to the AvaI site and includes the single PstI site and HpaI site. A notable feature of this sequence is the presence of tandem repeats of 124 residues beginning at the HpaI site and extending beyond the AvaI site. The sequence was determined independently by both the Maxam-Gilbert procedure applied to isolated restriction fragments, and by the chain-termination procedure applied to restriction fragments cloned in the single-stranded phage M13mp2 and purified by plaque selection.